Os gestores e as políticas públicas ambientais na capacitação para a promoção da sustentabilidade municipal: o caso de Fortaleza-CE. - Costa, Débora Cristina Capistrano da (2012)
The environmental politics depend on the popular participation and on the public administrators in the conduction of the environmental plan process, in the definition of the strategic orientation of the town, state or country. The exercise of government followed by the precepts of sustainability requires an ethical compromise on the part of the competent management. So there is the questioning: are the public agents of Fortaleza-CE, properly prepared to follow the environmental norms guarding the equilibrium with the activities of economic development aiming to preserve the life quality of the population as well to achieve a more sustainable development? In that way, this work intends to analyze the organization of the environmental management carried out by the municipal Public Sector in the city of Fortaleza-CE after participation of representatives in the Qualification National Program of Environmental Agents and Counselors of the Environment National System. By the evaluating research, the results enabled to draw the features of the agent that acts in the Environment institutions of Fortaleza-CE and how is their management. Permitting the understanding of the actions of government of the city for environmental sustainability against the evolution of the concept of sustainable development and bringing the need to discuss the importance of the conception and implementation of a Environmental Management System (SGA) in the municipal Public Administration.